2016
DOI: 10.1021/acs.analchem.6b01981
|View full text |Cite
|
Sign up to set email alerts
|

Investigating the Role of the Stringent Response in Lipid Modifications during the Stationary Phase in E. coli by Direct Analysis with Time-of-Flight-Secondary Ion Mass Spectrometry

Abstract: Escherichia coli is able to rapidly adjust the biophysical properties of its membrane phospholipids to adapt to environmental challenges including starvation stress. These membrane lipid modifications were investigated in glucose starved E. coli cultures and compared to a ΔrelAΔspoT (ppGpp(0)) mutant strain of E. coli, deficient in the stringent response, by means of time-of-flight-secondary ion mass spectrometry (TOF-SIMS). Recent advances in TOF-SIMS, through the implementation of gas cluster ion beams (GCIB… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 56 publications
1
11
0
Order By: Relevance
“…In a previous study in our laboratory we observed an increase in cyclopropane containing lipids in carbon starved bacteria that was dependent on the presence of the global stress signaling compound ppGpp. 13 This increase in cyclopropane formation had previously been reported in GC-MS analysis but the SIMS experiments also suggested that the process occurred via the initial formation of the unsaturated fatty acids prior to cyclopropanation. These new results, showing a strong reduction in FA(cp19:0) upon loss of FabF, suggest that the FabF route to the formation of the FA(18:1) is strongly linked to the cyclopropane formation.…”
Section: ■ Results and Discussionsupporting
confidence: 67%
“…In a previous study in our laboratory we observed an increase in cyclopropane containing lipids in carbon starved bacteria that was dependent on the presence of the global stress signaling compound ppGpp. 13 This increase in cyclopropane formation had previously been reported in GC-MS analysis but the SIMS experiments also suggested that the process occurred via the initial formation of the unsaturated fatty acids prior to cyclopropanation. These new results, showing a strong reduction in FA(cp19:0) upon loss of FabF, suggest that the FabF route to the formation of the FA(18:1) is strongly linked to the cyclopropane formation.…”
Section: ■ Results and Discussionsupporting
confidence: 67%
“…Although cyclopropane modifications may seem insignificant, they have significant biological implications. Cyclopropane fatty acids (CFAs) are generated by the addition of a methylene group across the double bonds of unsaturated fatty acids (UFAs) of bacterial phospholipids. , This methylene group is derived from S -adenosylmethionine, and the in situ reaction of UFA to CFA is catalyzed by CFA synthase. During this reaction, the CFA retains the original stereochemistry of the UFA, whether cis or trans. , This reaction occurs in response to adverse environmental conditions, and it is common in various Gram-positive and Gram-negative bacterial species including Escherichia coli (E.…”
mentioning
confidence: 99%
“…The focus of the ion beam is continuously variable down to the minimum spot size, which for this GCIB is 2−3 μm as measured using the 20−80% signal rise or fall on the edge of a sharp feature in either SIMS or secondary electron images. 43 The ion gun has a series of selectable apertures that can be used to select current/spot size as required. The ion gun delivered 21 pA of DC current (measured in a Faraday cup on the sample holder) through a 100 μm aperture for the 30 μm per pixel imaging and approximately 2 pA through a 30 μm aperture for the 3 μm per pixel imaging.…”
Section: ■ Experimental Sectionmentioning
confidence: 99%